Thalloid Liverworts in Waterfall and Stream Habitats of Deli Serdang Regency, North Sumatera - Ferdinand Susilo; Dhea Fathanah Lbn Tobing; Rahmiati; Jamilah Nasution (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia is known as a country that has very abundant biodiversity, one of which is moss. Mosses are non-vascular plants, small in size, and play a crucial role in forest ecosystems as pioneer plants, water reservoirs, erosionreducers, bioindicators, andmedicinal resources. Theresearchaims tocollect data and information regarding liverwort species in Deli Serdang Regency, North Sumatra, specifically focusing on sampling points along rivers and waterfalls as potential habitats for liverwort life. Thalloid liverwort sampling was conducted using an exploratory survey method, which involved exploring along the courseof rivers and waterfalls. The research findings revealed 6 species of liverworts, consisting of 3 genera and classified into 2 families: Marchantiaceae (Marchantia with 4 species, Dumortiera with 1 species) and Metzgeriaceae (Metzgeria with 1 species). Commonly found species at the location include Dumortiera hirsuta, Marchantia paleacea, and Metzgeria, while the least encountered species are Marchantia treubii, Marchantia pinnata, and Marchantia emarginata.